Answer :

Take L.H.S



{2 cos A cos B = cos (A + B) + cos (A – B)}




= 2 cos x {cos 120° + cos 2x}


= 2 cos x {cos (180° - 60°) + cos 2x}


{cos (180° - A) = - cos A}


= 2 cos x (cos 2x - cos 60°)


= 2 cos 2x cos x – 2 cos x cos 60°



= cos 3x + cos x – cos x


= cos 3x = R.H.S.


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics